2021
DOI: 10.1093/gbe/evab115
|View full text |Cite
|
Sign up to set email alerts
|

Our Tangled Family Tree: New Genomic Methods Offer Insight into the Legacy of Archaic Admixture

Abstract: The archaic ancestry present in the human genome has captured the imagination of both scientists and the wider public in recent years. This excitement is the result of new studies pushing the envelope of what we can learn from the archaic genetic information that has survived for over 50,000 years in the human genome. Here, we review the most recent ten years of literature on the topic of archaic introgression, including the current state of knowledge on Neanderthal and Denisovan introgression, as well as intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 174 publications
(319 reference statements)
0
13
1
Order By: Relevance
“…Key to our understanding of differences between modern and archaic humans is an appraisal of the functional effects of non-coding variants that existed in the evolutionary past, but which are no longer extant in present-day populations (5, 6, 41, 94, 95). Most genomic approaches developed so far have focused on transcriptional (3133, 39, 40, 43) rather than post-transcriptional variant effects (but see (41) and (32)), are limited to studying introgressed variants associated with phenotypes in well-sampled modern human populations (4, 24, 35, 36, 38), and do not distinguish causal variants from linked variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key to our understanding of differences between modern and archaic humans is an appraisal of the functional effects of non-coding variants that existed in the evolutionary past, but which are no longer extant in present-day populations (5, 6, 41, 94, 95). Most genomic approaches developed so far have focused on transcriptional (3133, 39, 40, 43) rather than post-transcriptional variant effects (but see (41) and (32)), are limited to studying introgressed variants associated with phenotypes in well-sampled modern human populations (4, 24, 35, 36, 38), and do not distinguish causal variants from linked variants.…”
Section: Discussionmentioning
confidence: 99%
“…These genetic differences likely underlie many of the phenotypic differences between modern and archaic fossils, but also phenotypic differences not preserved in the fossil record (4,5). Remarkably, genomic analyses have revealed multiple admixture events between modern and archaic humans (6)(7)(8)(9)(10)(11)(12), notably during modern human expansion Out of Africa. These introgression events contributed about 2% Neanderthal ancestry to all non-African into human embryonic kidney (HEK) 293T cells, where they then undergo transcription followed by RNA splicing (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The high-quality ancient genomes from both Neanderthals and Denisovans ( Meyer et al 2012 ; Prüfer et al 2013 , 2017 ) further revealed that our ancestors not only overlapped with the archaic hominins in space and time during Out-of-Africa migrations, but also interbred with them, through a process known as archaic introgression. Subsequent work has shown that the genomic variants from archaic hominins played a key role in shaping the phenotypic and genotypic landscapes observed in modern humans ( Vernot and Akey 2014 ; Deschamps et al 2016 ; Gittelman et al 2016 ; Juric et al 2016 ; Wall and Brandt 2016 ; Ahlquist et al 2021 ), through adaptive introgression (AI). AI refers to a process by which adaptation occurs via genetic variants that were introgressed into the modern (recipient) population from the archaic (donor) population ( Dannemann et al 2016 ; Racimo et al 2017 ; Burgarella et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The surviving archaic segments in modern human genomes are likely not the product of a single admixture event, but instead reflect a complex history of multiple points of contact between humans and several archaic populations [ 19 , 21 23 ]. Numerous demographic models and distinct introgression events have been suggested to explain the interactions between modern and archaic humans, although none has been posited that encompasses all modern human populations and archaic humans [ 24 ]. Many studies focus on Europeans and East Asians as focal populations, or on a single population of interest, such as Papuans, who have one of the highest proportions of Denisovan ancestry worldwide [ 16 , 23 ].…”
Section: Introductionmentioning
confidence: 99%